IsoPuzzle: Development and Evaluation of an Ethno-Educational Serious Game - Thiago Emanuell V. Moura; Jaqueline Araújo Civardi; Mary Anne Vieira Silva; Luciana de Oliveira Berretta; Sergio Teixeira de Carvalho (Journal on Interactive Systems)
This study presents the development and evaluation of IsoPuzzle, a digital ethno-educational game that merges progressive isometric geometry challenges with Adinkra symbolism to integrate mathematical concepts and African cultural elements. Based on Game-Based Learning (GBL) and the PEED methodology, IsoPuzzle promotes collaboration and active stakeholder participation. Its evaluation, conducted via a structured questionnaire derived from frameworks such as SUS, MEEGA+, PAJDE, and IAQJEd, focused on three indicators: pedagogical engagement, accessibility and usability, and the impact of cultural immersion on player experience (PX). Results indicate that IsoPuzzle effectively combines mathematical abstraction with engaging visuals, enhancing cultural connections through the use of Adinkra symbolism. The analysis also identified areas for refinement, particularly related to instruction clarity and interface accessibility, indicating the need to improve navigational intuitiveness. The data proved reliable, with the educational dimension averaging 4.16 (SD = 0.91), the cultural dimension 3.78 (SD = 1.02), and the user experience 3.61 (SD = 1.08). Variations in device quality further influenced user experience, underscoring the need for multi-platform optimization. Overall, these findings provide valuable insights for refining digital teaching tools that strike a balance between mathematical rigor, cultural diversity, and interface efficiency.